Tổng hợp 21-acetat pregn-4,9(11)-dien-17α,21-diol-3,20-dion - Huy, Lưu Đức; Diệp, Nguyễn Thị; Thảo, Phạm Thị; Hùng, Lưu Đức (Vietnam Journal of Chemistry, 2014)
In this paper, we present the synthesis of the 21-acetate pregna-4,9(11)-diene-17α,21-diol-3,20-dione from 9α- hydroxy androstenedione, an important intermediate for synthesis of corticoids such as hydrocortisone and prednisolone. The structure of the product and its intermediates was examined by physical methods such as: IR, MS, 1H and 13C NMR. Keywords: 21-acetate pregna-4,9(11)-diene-17α,21-diol-3,20-dione, 9α-hydroxy androstenedione.